Factors That Determine the Performance Improvement of Small and Medium Enterprises in Jakarta - Sudirga, Rudy Santosa (Jurnal Entrepreneur dan Entrepreneurship, 2019)
The research of factors that determine the performance improvement of small and medium enterprises in Jakarta is based on the background of increasing small and medium enterprises sector in Jakarta. The benefits of this study are to find out what factors are most influential on the performance of small and medium enterprises in Jakarta. The authors took a number of 200 samples of small and medium enterprises in Jakarta, and the research data analysis technique is multiple regression with Structural Equation Modelling IBM SPSS Amos version 23. The results of respondents who answered the questions were dominated by respondents with a high school education background 152 people (76%), with ages ranging between 41–50 years 117 people (58.5%), and having income turnover above 90 million rupiah per month 122 people (61%), so it can be categorized that the majority of small and medium business entrepreneurs are educated in high school and are still in the productive age range. The results showed that the Business/Product Innovation, Business Competence, Business Capital, and Population had a significant effect on Business Performance, while variables Environmental Factors have no significant effect on Business Performance.